PREVALENSI STATUS KESEHATAN IBU HAMIL DI WILAYAH KERJA BLUD PUSKESMAS JATIBARU KOTA BIMA TAHUN 2025 - Rostinah; Nurbaniy; Sri Rahmawati; Kiki Rizki Aulia (Akademi Kebidanan Harapan Bunda Bima, 2025)
The research was conducted at the Jatibaru Health Center with the aim of presenting health data of pregnant women consisting of the age of pregnant women, gestational age, number of pregnancies, BMI, nutritional status, ownership of KIA books, ANC, health examination sites, ultrasound screening, systemic diseases, P4K, potential donors, birth history, complications of childbirth, history of the place of delivery, TT immunization screening, Hb, consumption of Fe tablets, and Iodine consumption. The research method used a survey conducted on 26 pregnant women. The results showed that the age of pregnant women was mostly 20-35 years (69.29%), gestational age was mostly 13-28 weeks (53.85%), BMI was mostly normal (53.85%), nutritional status seen from the upper arm circumference was mostly LILA ≥ 23.5 cm as much as 92.31%, most have KIA books (92.31%), ANC for pregnant women (100%), ultrasound screening is mostly carried out as much as 92.31%, systemic diseases in pregnant women are mostly absent at 65.38%, most of the prospective donors of pregnant women who meet the standard of 6 people are absent as much as 42.31%, most of the TT Immunization screening was 76.92%, most of the Hb levels of pregnant women > 11 gr % as much as 62%, 100% of pregnant women consumed Fe tablets, and 96.15% did not consume Iodine salts. Assistance efforts, counseling, and health checks can help overcome the high risk of pregnancy and improve the health of pregnant women.